COVID-19 disease severity and affectations in electroneuromyographic studies - E.A. Torres-Carranza; S. Reyes-Bravo; G. Hernández-Torres; A.Y. Longoria-Castro; O. Torres-Pineda; G Marin (Neurology Perspectives)
Introduction: Emerging research has highlighted COVID-19's profound impact on the nervous system, with ongoing debate regarding its severity and the emergence of peripheral neurological disorders. This study delves into the correlation between COVID-19 severity and electromyographic abnormalities in hospitalized patients, aiming to elucidate the nature and extent of neuromuscular dysfunction associated with the disease. Methods: In a retrospective, cross-sectional, observational study, we analyzed data from 170 patients treated at the North Physical Medicine and Rehabilitation Unit between July 2020 and April 2021. Post-COVID-19 patients underwent comprehensive motor and sensory nerve conduction studies. Spearman's correlation and Kruskal–Wallis tests were used to examine the relationship between disease severity and electromyographic findings. Results: Of the 170 patients in the study, 71.17% were male and 28.82% female, with an average age of 48 years; the subgroup of patients with severe clinical classification predominated at 68.23%. Spearman's correlation yielded values higher than 0.5 for all parameters analyzed concerning severity classification. A significant difference was found in the average of non-evoked motor and sensory nerves, motor nerves with latency, amplitude, and conduction velocity impairment, and affected muscles regarding critical classification. Conclusion: Our study showed a relationship between the severity of COVID-19 and an increase in non-evoked motor and sensory nerves, impaired motor nerve latency, amplitude, and velocity, and more affected muscles, particularly in critical cases. Resumen: Introducción: Investigaciones emergentes han destacado el profundo impacto del COVID-19 en el sistema nervioso, con un debate en curso sobre su gravedad y la aparición de trastornos neurológicos periféricos. Este estudio profundiza en la correlación entre la gravedad del COVID-19 y las anomalías electroneuromiográficas en pacientes hospitalizados, con el objetivo de dilucidar la naturaleza y el alcance de la disfunción neuromuscular asociada con la enfermedad. Métodos: En un estudio retrospectivo, transversal y observacional, analizamos datos de 170 pacientes atendidos en la Unidad de Medicina Física y Rehabilitación del Norte entre julio de 2020 y abril de 2021. Los pacientes posteriores a COVID-19 se sometieron a estudios completos de conducción nerviosa motora y sensorial. Las pruebas de correlación de Spearman y Kruskal-Wallis se utilizaron para examinar la relación entre la gravedad de la enfermedad y los hallazgos electroneuromiográficos. Resultados: De los 170 pacientes del estudio, 71.17% correspondieron al sexo masculino y 28.82% al femenino; con edad promedio de 48 años; predominando el subgrupo de pacientes con clasificación clínica grave con el 68.23%. Respecto a la correlación de Spearman se obtuvieron valores mayores a 0.5 en todos los parámetros analizados respecto a clasificación de severidad. Se encontró diferencia significativa en promedio de nervios motores y sensoriales no evocados, nervios motores con afectación en latencia, amplitud y velocidad de neuroconducción, y de músculos afectados respecto a clasificación crítica. Conclusiones: Nuestro estudio mostró una relación entre la gravedad de la COVID-19 y el aumento de los nervios motores y sensoriales no evocados, el deterioro de la latencia, amplitud y velocidad de los nervios motores, y más músculos afectados, especialmente en casos críticos. Sin embargo, no se encuentra correlación directa entre la gravedad de la COVID-19 y los hallazgos electroneuromiográficos en los pacientes evaluados.